1982
DOI: 10.1111/j.1469-8137.1982.tb03344.x
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen Diffusion in Pea

Abstract: SUMMARYFor roots growing in anoxic media the intercellular pore-space of the root cortex provides a channel for the diffusive flow of respiratory gases between shooot and root. Three methods were used in an attempt to quantify the diffusive resistance of this pore space (Rp) in pea. Two of the methods were based on polarographic measurements of oxygen flow through the roots: the 'cooling' and 'gas-mixture' methods; the third was based upon measurements of porosity and root geometry ('shape'). The last gave res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

1983
1983
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 19 publications
0
12
0
Order By: Relevance
“…The accumulation of diffusive resistance during root extension results in a decline in apical oxygen concentrations in the NWL species, pea (Armstrong, Healy & Webb, 1982;Armstrong, Healy & Lythe, 1983). Again, on a small sample of species it has been shown that rooting depth and FRP may be related (Yu, Stolzy & Letey, 1969).…”
Section: + + I ++ Imentioning
confidence: 95%
“…The accumulation of diffusive resistance during root extension results in a decline in apical oxygen concentrations in the NWL species, pea (Armstrong, Healy & Webb, 1982;Armstrong, Healy & Lythe, 1983). Again, on a small sample of species it has been shown that rooting depth and FRP may be related (Yu, Stolzy & Letey, 1969).…”
Section: + + I ++ Imentioning
confidence: 95%
“…In Figure 6 these results have been plotted against root length. Also presented in the same figure for comparison is the relationship between pore-space resistance and length (Armstrong et al, 1982). The magnifying effect that respiration and leakage of primary root and laterals have on the diffusive resistance as observed from the electrode position is clearly Primory root length (cm) Fig.…”
Section: Apical Oxygen Concentrationsmentioning
confidence: 94%
“…Meteor) were reared under sterile conditions on a nutrient 1 % agar medium in 250 ml measuring cylinders. Details of sterilization, and transplantation have been described elsewhere (Healy, 1975;Armstrong, Healy and Webb, 1982). Plants were removed for an assessment of their ventilating powers as required by extracting agar and plant en bloc.…”
Section: Plant Materialsmentioning
confidence: 99%
See 2 more Smart Citations